Evaluation of different injectors-swirl configurations on combustion and emissions characteristics in a medium-duty compression ignition diesel engine. (May 2023) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Guzmán, María Gabriela
To regulate emissions and reach efficiency values closer to theoretical limits in heavy and medium-duty vehicles the incremental improvement of the combustion engine is necessary as other options, like electrical powertrains, remain in the early stages of their development for such load demands. The objective of this work is to evaluate the effect on emissions and performance of three different injectors – with two flow rates (1300 and 1500 cm 3 /min) and three different hole numbers (7, 9, and 10) – coupled with two levels of swirl ratio (1.81 and 1.05) under experimental stationary conditions. Following this, a merit function strategy is developed and used to determine the hardware combination that provides the best advantage regarding the tradeoff between emissions and fuel consumption based on criteria that considers prospective regulations and the current performance of the hardware. The results obtained from this work indicate that a low flowrate injector, coupled with a cylinder-head that achieves a swirl ratio of 1.81 performs the best among the tested hardware combinations, providing reductions of at least 2 g/kWh of indicated specific fuel consumption while NOx emissions are comparable with the other tested hardware combinations and soot emissions have almost negligible values (under 6 mg/kWh for all operating conditions).